Extraction of 2′-O-apiosyl-6′-O-crotonic acid-betanin from the ayrampo seed (Opuntia soehrensii) cuticle and its use as an emitting layer in an organic light-emitting diode - Rivera Tito, Harry Anderson; Hernández-Sosa, Gerardo; Romero-Nieto, Carlos; Regulska, Elzbieta; Jürgensen, Nils; Zimmermann, Johannes; Salazar-Salinas, Karim; Caceda, María Esther Quintana (RSC Advances, 2020)
The molecule 2′-O-apiosyl-6′-O-crotonic acid-betanin (called Achkiy) was obtained after an ecofriendly and low-cost purification process of the extract from the ayrampo seed cuticle. Results from EDS give us an idea of the organic elements present in the ayrampo cuticle layer composed of carbon, oxygen and nitrogen. Further characterization analysis of ayrampo extract by Fourier Transform Infrared Spectrophotometry (FTIR) corroborated the presence of characteristic functional groups corresponding to carboxyl, carbonyls, hydroxyls and secondary amines. On the other hand, we have confirmed by absortion peak the glucose, apiosyl, crotonic acid and betanin at 227 nm, 276 nm, 291 nm and 534 nm bands respectively. Mass Spectrometry (MS) characterization was used finally to identify the electroactive Achkiy molecule. This molecule was tested in an Organic Light Emitting Diode (OLED) achieving a luminance of 4.8 Cd m−2 when bias voltage of 16.5 V and a current of 34.1 mA was applied. In addition, the irradiance generated by the Achkiy layer reaches a value of ≈ 113.3 μW m−2 emitting light with a λ ≈ 390.10 nm. These preliminary results report an interesting molecule extracted from a natural pigment wich emits light in the blue region.